The role of infographic learning media in increasing literature interest of SMP students during pandemic - Nuke Rizkiyanti; Muktiarni Muktiarni; Jonah Mupitah (Universitas Pendidikan Indonesia, 2021)
The beginning of 2020 is a time when the world undergoes enormous changes. Enactment deployment virus Covid-19 as a pandemic by the WHO (World Health Organization) makes almost all sectors of life required to adapt to activities without meeting face to face. No exception in the sectors of education, teaching and learning activities are also activities due to this pandemic situation. The changes felt by the training staff and students are great, especially in terms of literacy. Children's literacy interest in Indonesia is still very low, this is certainly a concern that must be considered given the importance of literacy. During the pandemic, which relies on technology, it must also be used as a way to improve student literacy in Indonesia. The use of learning media provided online can certainly be used as an effort to increase student literacy interest. This research is motivated by the low interest in student literacy and distance learning. Therefore, researchers are looking for efforts through the use of learning media to increase student literacy interest, namely by using infographics. The purpose of this study was to determine how far the level of students' literacy understanding after using infographics as a medium for delivering subject matter. This research is descriptive qualitative, with a phenomenological approach as well as conducting observations and interviews. The research was conducted on students of SMPN 2 Margahayu, Bandung Regency. The results of this study indicate the effectiveness given in the use of infographics as learning media to increase student literacy interest.